Using Blender 3D Node-Based Compositor to Replicate Video Home System Visual Analog - Theophilus Ceezario Christianto; Mohammad Arifian Rohman; Samuel Gandang Gunanto (Jurnal Ilmiah Multimedia dan Komunikasi, 2026)
Due to its unique analog visual quality and ability to evoke nostalgia, the visual esthetics of the Video Home System (VHS) are once again widely used in various digital works. The aim of this research is to assess how well the Node-Based Compositor in Blender 3D replicates VHS visual features in an integrated compositing approach. This study employs a Practice-Based Research methodology through seven experimental phases that investigate node configurations to produce VHS visual features, which were then verified by thirty participants. According to the study's findings, every respondent (100%) stated that the experimental results accurately depicted VHS-style analog graphics, with 53.3% providing full validation and 46.7% providing conditional validation. These results indicate that the Node-Based Compositor in Blender 3D can be used to replicate analog graphics in a VHS manner while providing more effective and integrated compositing techniques. This study offers a different approach to digital animation creation and advances research on the application of Node-Based Compositor in analog visual reproduction.